The data warehouse mentor : practical data warehouse and business intelligence insights - Laberge, Robert , 1961- (McGraw-Hill, 2011)
"Proven strategies for implementing the right data warehouse and business intelligence solutions for current and future business needs in the data warehouse mentor: practical data warehouse and business intelligence insights, business intelligence and data warehousing expert Robert Laberge explains the components and different alternatives in building a data warehouse and describes pros and cons for choosing one path over another. Building a data warehouse is unique for each organization but can be guided by the author's years of knowledge obtained from working on many differing data warehouse and business intelligence environments in organizations around the world.The book covers practical and technical aspects of current data warehouse and business intelligence issues with views on realistic solutions within the management and technical arenas. Data warehousing topics are first presented from a high-level overview to ensure the terminology and context is understood, and are then covered in deeper detail to clarify the specifics. These topics all pertain to data warehousing, business intelligence, and performance management.The data warehouse mentor explains the proper implementation of the many available technologies and practices shares the author's nearly 30 years of data warehouse and business intelligence experience in more than 20 countries worldwide mentors you to success in determining and deploying the most effective data warehouse and business intelligence solutions for your business Helps you anticipate future data requirements and usage to ensure the design and build environment for your solution is flexible and open to change complete coverage: data warehouse and business intelligence overview; data in the organization; reasons for building; business intelligence and data warehouse strategy - The plan; project resources - Roles and insights; write it up - Overview; business intelligence: data marts & usage; enterprise data models; data warehouse architecture; ETL and data quality; project planning; working scenarios - Hands on; data governance; post project review" -- Provided by publisher